Can Advocates’ Legal Culture in Civil Law Enforcement Drive Reform in Indonesia’s Modern Justice System? - Dian Latifiani; Baidhowi Baidhowi; Pratama Herry Herlambang; Farkhan Radyafani Winarno; Ahmad Habiburrahman (Journal of Law and Legal Reform, 2024)
This study examines the urgent need to reform the legal culture of advocates in Indonesia, specifically in relation to the use of e-court and e-litigation systems in civil law enforcement. These systems were designed to streamline legal processes, offering faster, cheaper, and more accessible trials for material parties. However, advocates have been slow to adopt these technologies, often sticking to traditional methods, which undermines their potential effectiveness. The novelty of this research lies in its exploration of how the legal culture of advocates can be reformed to better leverage e-court and e-litigation. Rather than focusing solely on the technical aspects of these systems, the study emphasizes the socio-legal implications of such reforms. Advocates, as both legal professionals and agents of social change, play a critical role in bridging the gap between new technologies and the material parties they represent. This research contributes to the development of civil procedural law and aims to improve the legal culture of both advocates and clients. Using a qualitative, socio-legal approach, the study gathers data through interviews, observations, document analysis, and personal experiences. The urgency of this reform is underscored by the need for advocates to fully embrace their role in Indonesia’s digital transformation of justice. The study also examines how regulatory tools like PERMA No. 1 of 2019 and No. 7 of 2022 can support these reforms, ultimately driving systemic change in Indonesia’s legal culture and enhancing the effectiveness of e-court and e-litigation.